2015
DOI: 10.1007/s12275-015-5454-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced method for microbial community DNA extraction and purification from agricultural yellow loess soil

Abstract: In this study, novel DNA extraction and purification methods were developed to obtain high-quantity and reliable quality DNA from the microbial community of agricultural yellow loess soil samples. The efficiencies of five different soil DNAextraction protocols were evaluated on the basis of DNA yield, quality and DNA shearing. Our suggested extraction method, which used CTAB, EDTA and cell membrane lytic enzymes in the extraction followed by DNA precipitation using isopropanol, yielded a maximum DNA content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…To compensate for the low DNA extraction efficiency of lysozyme for most Gram-negative bacteria, a treatment step with proper ultrasonic disruption was used in the CLU method, which could break down the cell walls of Gram-negative bacteria and allowed good liberation of the DNA. In addition, the incubation temperature during the process of lysozyme lysis was usually maintained at 37 °C in previous studies (Kathiravan et al 2015 ; Bag et al 2016 ). However, some investigators noted that the activity of lysozyme from egg whites increased gradually with increasing temperature within the range of 25–65 °C (Liu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compensate for the low DNA extraction efficiency of lysozyme for most Gram-negative bacteria, a treatment step with proper ultrasonic disruption was used in the CLU method, which could break down the cell walls of Gram-negative bacteria and allowed good liberation of the DNA. In addition, the incubation temperature during the process of lysozyme lysis was usually maintained at 37 °C in previous studies (Kathiravan et al 2015 ; Bag et al 2016 ). However, some investigators noted that the activity of lysozyme from egg whites increased gradually with increasing temperature within the range of 25–65 °C (Liu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, conventional culture-dependent techniques were used; however, only a small percentage of the bacterial flora was identified (Kathiravan et al 2015 ). Recently, molecular techniques, including but not limited to denatured gradient gel electrophoresis (Li et al 2011 ), fluorescence in situ hybridization (Hoffmann et al 2006 ) and 16S rDNA high-throughput sequencing (Gajardo et al 2016 ), have been used successfully to analyze the complex microbial community from fish intestines.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, an increasing number of studies have focused on the gut microbiota of fish (Narrowe et al., ; Xia et al., ). In early studies, conventional culture‐dependent techniques were used; however, only a small percentage of the resulting bacterial flora was identified (Kathiravan et al., ). Recently, new technologies based on meta‐genomics/high‐throughput sequencing have been developed and successfully applied to analyzing the complex bacterial ecosystem of the gut.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Accordingly, the isolation of high-quality DNA that covers the whole microbial diversity in the original sample was phrased as a limiting step for the construction of metagenomic libraries and other DNA based metagenomic projects. 6 …”
Section: Introductionmentioning
confidence: 99%
“…In these regards, many studies have reported the development of methods and even commercial kits for mDNA extraction. 5 , 6 However, still, there is a surge in developing, improving, and optimizing new or current protocols for mDNA extraction from different types of samples. A metagenomic DNA extraction must be followed by a quality control of the extracted DNA.…”
Section: Introductionmentioning
confidence: 99%